1983
DOI: 10.3109/03009748309102905
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Nerve Function in Rheumatoid Arthritis of Varying Severity

Abstract: Autonomic nerve function was evaluated by deep breathing and tilt table tests in 17 patients with rheumatoid arthritis (RA) and in 24 healthy control subjects. The results showed that all RA patients had increased heart rates at rest, irrespective of the severity of the disease. Patients with severe RA had increased systolic and diastolic blood pressures before and after tilting. Pronounced abnormalities in the immediate heart rate reaction to tilting indicating autonomic neuropathy (AN) were also demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(32 citation statements)
references
References 13 publications
2
28
0
2
Order By: Relevance
“…Several investigators assessed cardiovascular autonomic nerve function in RA patients and observed cardiovascular autonomic nervous system dysfunction [5][6][7][8] .Similar trends for greater fall of SBP in RA patients was noted by Louthreno et al 5 .and less rise of DBP was reported by Sandhu and Allen 6 whereas similar results in both parameters were also reported 2 .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Several investigators assessed cardiovascular autonomic nerve function in RA patients and observed cardiovascular autonomic nervous system dysfunction [5][6][7][8] .Similar trends for greater fall of SBP in RA patients was noted by Louthreno et al 5 .and less rise of DBP was reported by Sandhu and Allen 6 whereas similar results in both parameters were also reported 2 .…”
Section: Discussionsupporting
confidence: 58%
“…Recently, orthostatic hypotension was found in 8% of RA patients 2 . Though, few studies investigated autonomic function in RA [5][6][7][8][9] , the effect of duration of RA on 10 with duration of disease from one to ten years were enrolled from the Rheumatology wing of the outpatient department of medicine of BSMMU, Dhaka. Age and BMI matched 30 apparently healthy sedentary females were control.…”
mentioning
confidence: 99%
“…Clinically, there are multiple reports of autonomic dysregulation in both juvenile chronic and RA, such as increased resting heart rates and elevated levels of urinary NE metabolites [353] and augmented SNS reflex responses to orthostatic stress [354], the valsalva maneuver [354], deep breathing [355], pupil size [355] and perspiration [356]. These reports suggest increased sympathetic tone.…”
Section: Sympathetic Regulation Of Autoimmune Diseasesmentioning
confidence: 96%
“…Sandhu and Allen 13 in 2004 observed lower value of 30 th :15 th ratio whereas others rather found higher values. 6 Leden et al 8 also found abnormal heart rate response to standing in patients with Rheumatoid Arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4] The increased incidence of sudden cardiac death in these group of patients may be related to the decreased vagal drive to the heart. 5 In RA, researchers of different countries [8][9] .Lower values of heart rate response to valsalva maneuver, heart rate response to deep breathing and heart rate response to standing (30 th :15 th ratio) were reported in patients with RA in comparison with those of healthy control. 10- 13 Opposite finding was also reported by some investigators who did not find any cardiovascular autonomic abnormality in patients with rheumatoid arthritis when compared with those of healthy control 14 .…”
mentioning
confidence: 99%